Roles of circular RNAs in immune regulation and autoimmune diseases - Zhou, Zheng; Sun, Bao; Huang, Shiqiong; Zhao, Lingling (Cell death & disease, 2019)
Circular RNAs (circRNAs), as a novel class of endogenously expressed non-coding RNAs (ncRNAs), have a high stability and often present tissue-specific expression and evolutionary conservation. Emerging evidence has suggested that circRNAs play an essential role in complex human pathologies. Notably, circRNAs, important gene modulators in the immune system, are strongly associated with the occurrence and development of autoimmune diseases. Here, we focus on the roles of circRNAs in immune cells and immune regulation, highlighting their potential as biomarkers and biological functions in autoimmune diseases, such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), multiple sclerosis (MS), primary biliary cholangitis (PBC), and psoriasis, aiming at providing new insights into the diagnosis and therapy of these diseases.